At the zoo : telling time by the quarter hour - Proctor, Alice, 1967- (Pleasantville, NY : Weekly Reader Pub., 2008)
Photographs and simple text teaches young readers how to tell time.
Telling time -- Quarter past -- Quarter to -- My day at the zoo -- Morning at the zoo -- Feeding time at the zoo -- Afternoon at the zoo -- Evening and night at home -- Time facts -- Times to remember.
Previously published: Great Britain : ticktock Media Ltd., 2007.
3.3
K-3
Keywords: Day -- Juvenile literature; Time -- Juvenile literature; Zoos -- Juvenile literature; Day; Time; Zoos; Day; Time; Zoos; Readers (Elementary).